The City Government's Role In Begging - Hardi Fardiansyah; Nanda Dwi Rizkia (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The purpose of this study is to ascertain how the Bandung municipal government interacts with homeless persons and to pinpoint the factors that support and impediment this interaction. This study employs a descriptive methodology and is qualitative in nature. The research subjects include the Mayor of Bandung, the Director of the Bandung City Social Service, and the sprawl of the City of Bandung. Based on the results of the data analysis, it is feasible to draw the following conclusion: The 2019 Bandung City Regional Regulation Concerning the Treatment of Vagabonds and the Homeless regulates how the municipal government is to handle gepeng. Social services aid in efforts to rehabilitate society. According to Article 16 of the 2019 Bandung City Regional Regulation, efforts to end homelessness are conducted in four different ways: prevention, repression, social rehabilitation, and reintegration activities. The central government's support, the 2019 Regional Regulation, the existence of non-governmental groups, and community support all contribute to the Bandung City Government's attempts to manage sprawl. Two barriers are the sluggish homeless culture and the cash-on-hand culture.